Correlates of physical activity in people living with psychotic illness. (24th May 2016) - Suetani, S.; Waterreus, A.; Morgan, V.; Foley, D. L.; Galletly, C.; Badcock, J. C.; Watts, G.; McKinnon, A.; Castle, D.; Saha, S.; Scott, J. G.; McGrath, J. J.
Abstract : Objective: In the light of the high prevalence of physical comorbidities in people with psychotic illness, there is a need to explore modifiable risk factors that may contribute to this disease burden. The benefits of physical activity to both physical and mental health have been well established. We aimed to examine the prevalence and correlates of physical activity in a national sample of adults living with psychotic illness. Methods: Physical activity was assessed in 1801 people using the International Physical Activity Questionnaire. Participants were dichotomised into low and moderate–high physical activity groups and associations between physical activity and a range of sociodemographic, clinical and physical comorbidity variables were examined using logistic regression. Results: More than half the participants were categorised in the moderate–high physical activity group with nearly half of the sample engaged in physical activity every day. There were significant associations between low physical activity and older age, unemployment, educational non‐participation, antipsychotic medication use, social dysfunction, self‐reported loneliness and obesity. However, there was no significant association between physical activity and sex, psychosis type, illness duration, physical comorbidity or negative symptoms. Conclusion: The findings from this study may inform future interventions designed to increase physical activity in people with psychotic illness.